2018
DOI: 10.1016/j.psyneuen.2018.04.017
|View full text |Cite
|
Sign up to set email alerts
|

When couples’ hearts beat together: Synchrony in heart rate variability during conflict predicts heightened inflammation throughout the day

Abstract: Hostile conflict in marriage can increase risks for disease and mortality. Physiological synchrony between partners-e.g., the linkage between their autonomic fluctuations-appears to capture engagement, or an inability to disengage from an exchange, and thus may amplify the health risks of noxious interactions such as marital conflict. Prior work has not examined the unique health correlates of this physiological signature. To test associations between couples' heart rate variability (HRV) synchrony during conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 54 publications
7
63
0
Order By: Relevance
“…As such PL may provide a more sensitive measure than self-reports for interpersonal processes that are not readily accessible to awareness for many people ( Butler and Randall, 2013 ). Third, associations have been found between PL and mental and physical health ( Butler, 2017 ; Wilson et al, 2018 ), suggesting that if we had a better understanding of PLs, it may offer novel interpersonal interventions.…”
Section: Introductionmentioning
confidence: 99%
“…As such PL may provide a more sensitive measure than self-reports for interpersonal processes that are not readily accessible to awareness for many people ( Butler and Randall, 2013 ). Third, associations have been found between PL and mental and physical health ( Butler, 2017 ; Wilson et al, 2018 ), suggesting that if we had a better understanding of PLs, it may offer novel interpersonal interventions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, as noted above, moderate initial vagal withdrawal followed by robust recovery may be an optimal profile. Associations between interacting partners' changing levels of vmHRV are an emerging research focus (e.g., Helm, Sbarra, & Ferrer, 2014;Wilson et al, 2018), quantified to index the degree of synchrony (i.e., concurrent changes) or co-regulation (i.e., lagged associations in which one partner's fluctuating vmHRV predicts the other partner's responses). Such associations are potentially important, but the processes that produce them and the outcomes they predict likely depend on the contexts in which they occur (e.g., conflict discussions vs. warm interactions).…”
Section: Additional Emerging Questionsmentioning
confidence: 99%
“…While partners interact, their stress levels can also synchronize such that their reactivity rises and falls together, thus impacting both partners’ psychological and biological responses. For instance, one study showed that when couples’ cardiovascular reactivity synchronized during a marital disagreement, both partners had greater negative affect reactivity and higher inflammation (Wilson et al, 2018). Lastly, couples regulate each other’s emotional responses to stress (Butler, 2015).…”
Section: Stress Reactivity At the Dyadic Levelmentioning
confidence: 99%